2020
DOI: 10.1590/1678-4685-gmb-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Identification of environmental and genetic factors that influence warfarin time in therapeutic range

Abstract: Warfarin is an oral anticoagulant prescribed to prevent and treat thromboembolic disorders. It has a narrow therapeutic window and must have its effect controlled. Prothrombin test, expressed in INR value, is used for dose management. Time in therapeutic range (TTR) is an important outcome of quality control of anticoagulation therapy and is influenced by several factors. The aim of this study was to identify genetic, demographic, and clinical factors that can potentially influence TTR. In total,422 patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Hypertension was a predominant concurrent illness in our study cohort and is known to be a major illness among Africans, most of the time asymptomatically in males (Mutowo et al, 2015 ). Similarly, hypertension was a predominant comorbidity in similar studies in Sweden (Rydberg et al, 2020 ), South Africa (Njovane and Fasinu, 2012 ; Sonuga et al, 2016 ), and Brazil (Botton et al, 2020 ).…”
Section: Discussionmentioning
confidence: 70%
“…Hypertension was a predominant concurrent illness in our study cohort and is known to be a major illness among Africans, most of the time asymptomatically in males (Mutowo et al, 2015 ). Similarly, hypertension was a predominant comorbidity in similar studies in Sweden (Rydberg et al, 2020 ), South Africa (Njovane and Fasinu, 2012 ; Sonuga et al, 2016 ), and Brazil (Botton et al, 2020 ).…”
Section: Discussionmentioning
confidence: 70%
“…Earlier studies have shown that a number of demographic, clinical, and genetic factors all affect the warfarin maintenance dosage in patients. 7,8 A few warfarin dosing algorithms have incorporated genetic and environmental factors that affect stable warfarin dose requirements and predict the efficacy of treatment. 3,9 In particular, genetic variations have been found to play a key role in influencing the maintenance dose of warfarin.…”
Section: Introductionmentioning
confidence: 99%